BUDAYA PEMBELAJARAN KOLABORATIF DI ERA DIGITAL - Nurjanah Nurjanah; Lailatul Fitri; R. Kinkin Siti Sa’adah (Journal Educatione, 2024)
The digital era has brought significant transformations across various aspects of life, including education. One of the major changes is the shift from conventional learning models to a culture of collaborative learning supported by digital technology. This study aims to examine how the culture of collaborative learning evolves in the digital era, the factors that influence its effectiveness, and its implications for both students and educators. The method used in this research is a literature review that collects and analyzes various scholarly sources related to this topic. The results of the study indicate that the culture of collaborative learning in the digital era can enhance student engagement and motivation, strengthen social skills, and promote creative and innovative problem-solving. Digital technology, such as e-learning platforms, social media, and online collaborative tools, plays a key role in facilitating interaction and collaboration among learners. However, the successful implementation of collaborative learning also heavily depends on the readiness of technological infrastructure, the digital competence of educators, and the support of progressive educational policies. The implications of these findings suggest that to optimize the benefits of a collaborative learning culture in the digital era, educational institutions need to invest in technological development and digital competency training for educators. Additionally, an adaptive and flexible pedagogical approach is required to accommodate the diverse needs and learning styles of students.